It is not la vie en rose: new insights from Graziani's theory of the monetary circuit - Marco Veronese Passarella (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
The aim of this paper is twofold. First, it shows how a standard stock-flow consistent model (SFCM) can be modified to embed some fundamental insights from Graziani's theory of the monetary circuit (TMC). Second, it aims to address some common misconceptions about the TMC. More precisely, it is argued that: (a) a market-clearing price mechanism does not necessarily imply a neoclassical-like closure of the model; (b) the ways in which SFCMs and the TMC define bank loans are mutually consistent, although they are based on different accounting periods; (c) consumer credit is final finance, not initial finance; (d) the paradox of profit is not a logical conundrum, but an abstract counter-factual that allows the shedding of light on a neglected role of government spending; and (e) overall, the TMC can be regarded as a 'Marxian' rendition of Keynes's method of aggregates.
Keywords: E11; E12; E16; E17; 330; Theory of the monetary circuit; Stock-flow consistent models; Macroeconomics; Monetary economics